A Vast Expansion, Yet a Sorry Infrastructure: A Paradox of the Decolonization of Indonesian Education, c. 1950s - Agus Suwignyo (Universitas Gadjah Mada, 2021)
The multitude of infrastructural problems in the Indonesian educational sector which had to be dealt with during the 1950s was counterpointed by the sector’s massive expansion. The aim of this paper is to explore this paradox in the framework of Indonesian decolonization. The government policy was to greatly expand education at all levels because it believed education was a gateway to “fulfilling independence (mengisi kemerdekaan)”. This paper argues that this expansion was a strategy of decolonization by which the education legacy of the colonial past was to be delegitimized. However, severe budgetary limitations, and a lack of infrastruture and facilities forced the government to continue its dependence on the inherited colonial education facilities and on foreign aid, hence made the strategy of decolonization unrealized in this process of expansion.